2021
DOI: 10.3389/fpsyg.2021.645788
|View full text |Cite
|
Sign up to set email alerts
|

Brief Interventions Influence the Quantity and Quality of Caregiver-Child Conversations in an Everyday Context

Abstract: Reading and arithmetic are difficult cognitive feats for children to master and youth from low-income communities are often less “school ready” in terms of letter and number recognition skills (Lee and Burkam, 2002). One way to prepare children for school is by encouraging caregivers to engage children in conversations about academically-relevant concepts by using numbers, recognizing shapes, and naming colors (Levine et al., 2010; Fisher et al., 2013). Previous research shows that caregiver-child conversation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…1d). Similarly, when signs emphasizing conversations about number, color, and shape were placed around a food pantry in the Midwest of the United States, adults shopping with children engaged in significantly more talk about these academically relevant topics compared to when signs emphasized non-academic topics (Shivaram et al, 2021). However, to date studies have only shown that prompting parents to engage in such conversations indeed leads to increases in math conversations.…”
Section: Parent-child Activities That Can Be Integrated Into Everyday...mentioning
confidence: 99%
“…1d). Similarly, when signs emphasizing conversations about number, color, and shape were placed around a food pantry in the Midwest of the United States, adults shopping with children engaged in significantly more talk about these academically relevant topics compared to when signs emphasized non-academic topics (Shivaram et al, 2021). However, to date studies have only shown that prompting parents to engage in such conversations indeed leads to increases in math conversations.…”
Section: Parent-child Activities That Can Be Integrated Into Everyday...mentioning
confidence: 99%
“…Findings on the importance of parental math talk have generated interest in identifying ways of increasing both its quantity and quality. One approach used in this experimental work is to explicitly direct parent’s attention to the opportunities for discussing math with children (e.g., Braham et al, 2018; Eason & Ramani, 2020) and to scaffold their interactions with prompts or guidance (e.g., Hanner et al, 2019; Shivaram et al, 2021; Vandermaas-Peeler et al, 2012; Vandermass-Peeler, Ferretti, & Loving, 2012). For instance, Hanner et al (2019) placed signs in grocery stores prompting 2-to-5-year-olds’ parents to talk about math and providing math-related questions they could ask (e.g., How many glasses of milk do you drink in a day?).…”
Section: Ways To Increase Parent Math Talkmentioning
confidence: 99%
“…Indeed, in Philadelphia, members of the community became part of the scientific team to research the impact of the installations on caregiver-child behavior and child outcomes (Hassinger-Das et al, 2020. Evaluation of PLLs in previous work reveals that PLL outcomes are measurable and align with our goals of increasing adult-child interaction quality and language use, building positive attitudes and beliefs about playful learning, 10.3389/fpsyg.2022.933320 encouraging ownership of local spaces, and increasing civic engagement (Ridge et al, 2015;Hanner et al, 2019;Bustamante et al, 2020;Hassinger-Das et al, 2020;Gaudreau et al, 2021;Shivaram et al, 2021).…”
Section: Evaluating the Modelmentioning
confidence: 99%